Factors Associated with Poor Quality of Life in Lung Cancer Patients Undergoing Chemotherapy in Erbil City - Dler Hamad Ismael (Hawler Medical University, 2023)
Background and aims: Lung cancer is one of the most prevalent types of cancer in the world, and the aim of the study was to determine the quality of life. and its related factors in lung cancer patients undergoing chemotherapy. Methods: A descriptive cross-sectional study design was conducted in Iraq in 2022 on 100 cancer patients undergoing chemotherapy who were randomly collected in Rizgary Teaching Hospital and Nanakaly Hospital for blood disease and cancer. The instrument used for data collection consisted of demographic and medical data (age, gender, educational level, marital status, occupation, economic status, residency, cigarette smoking, family history, stages of lung cancer, and types of lung cancer), another section was the functional assessment of cancer therapy-lung questionnaire (FACT-L), specifically designed for the measurement of quality of life in patients with lung cancer.  Categorical data were presented as frequency and percentage and the mean± SD was calculated for continuous data, independent t-test, and Chi-square test was also used; Binary logistic regression was run to determine the effect of the predictors on poor quality of life in lung cancer patients a P-value ≤0.05 was considered statistically significant. Results: The overall quality of life was poor (59%), the mean± SD for Functional Assessment of Cancer Therapy Lung Cancer Subscale (FACT-L) was 66.19 ± 10.54, and Trial Outcome Index (TOI) was 39.77±5.51, The following variables were associated with a poor quality of life: age >50 (P-value =0.020, OR= 2.47), female (P-value =0.006, OR= 3.02), uneducated (P-value =0.0005, OR= 1.86), ex-smoker (P-value =0.040, OR= 2.14), insufficient income (P-value =0.037, OR= 2.69). Conclusion: The quality of life of lung cancer was lower in physical well-being, functioning well-being, and lung cancer subscale compared to social/family well-being, and emotional well-being, as generally, the quality of life of most lung cancer patients was poor.